Factors Associated with Mortality Among Hospitalized Adults with COVID-19 Pneumonia at a Private Tertiary Hospital in Tanzania: A Retrospective Cohort Study - Kassam, Nadeem; Aghan, Eric; Aziz, Omar; Mbithe, Hanifa; Hameed, Kamran; Shah, Reena; Surani, Salim; Orwa, James; Somji, Samina (International journal of general medicine, 2021)
The emergence of the novel coronavirus disease 2019 (COVID-19) has caused millions of deaths worldwide. There has been paucity of data for hospitalized African patients suffering from COVID-19. This study aimed to identify factors associated with in-hospital mortality in patients suffering from COVID-19 in Tanzania. This was a single center, retrospective, observational cohort study in adult patients hospitalized with confirmed COVID-19 infection. Demographics, clinical pattern, laboratory and radiological investigations associated with increased odds of mortality were analyzed. Of the 157 patients, 107 (68.1%) patients survived and 50 (31.8%) died. Mortality was highest in patients suffering with severe (26%) and critical (68%) forms of the disease. The median age of the cohort was 52 years (IQR 42-61), majority of patients were male (86%) and of African origin (46%), who presented with fever (69%), cough (62%) and difficulty in breathing (43%). Factors that were associated with mortality among our cohort were advanced age (OR 1.07, 95% CI 1.03-1.11), being overweight and obese (OR 9.44, 95% CI 2.71-41.0), suffering with severe form of the disease (OR 4.77, 95% CI 1.18-25.0) and being admitted to the HDU and ICU (OR 6.68, 95% CI 2.06-24.6). The overall in-hospital mortality was 31.8%. Older age, obesity, the severe form of the disease and admission to the ICU and HDU were major risk factors associated with in-hospital mortality.